Hyperparathyroidism in Hemodialyzed Patients – Relation to Melatonin and Reproductive Hormones Before and After Parathyroidectomy - Kancheva, Radmila; Zofkova, Ivana; Hill, Martin; Dusilova-Sulkova, Sylvie; Kancheva, Ludmila; Rojdmark, Sven; Parizek, Antonin; Duskova, Michaela; Paluch, Zoltan; Cirmanova, Veronika; Starka, Luboslav (IntechOpen, 2012)
None